1992
DOI: 10.1016/0735-1097(92)90378-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive thrombolytic therapy for angioplasty in ischemic rest angina: Results of a double-blind randomized pilot study

Abstract: These data suggest a possible role for intracoronary urokinase during angioplasty for unstable angina. The lack of effect after infarction may represent a greater thrombus burden or degree of plaque disruption. A trial utilizing higher doses of urokinase in a larger patient group is in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In this situation, the administration of intracoronary thrombolytic agents along with redilatation has been reported to improve angiographic and clinical success.5-8 We previ-ously published the results of a small randomized, double-blind pilot study assessing the role of small doses of intracoronary urokinase as prophylaxis immediately before angioplasty for ischemic rest angina. 9 This study suggested that the formation of intracoronary thrombus after angioplasty could be decreased by intracoronary urokinase, although acute closure and in-hospital clinical events were similar to those in patients treated with placebo. To further assess the role of thrombolytic therapy in this circumstance, a larger trial was undertaken with higher doses of urokinase and monitoring of heparin therapy with activated coagulation times.…”
mentioning
confidence: 92%
“…In this situation, the administration of intracoronary thrombolytic agents along with redilatation has been reported to improve angiographic and clinical success.5-8 We previ-ously published the results of a small randomized, double-blind pilot study assessing the role of small doses of intracoronary urokinase as prophylaxis immediately before angioplasty for ischemic rest angina. 9 This study suggested that the formation of intracoronary thrombus after angioplasty could be decreased by intracoronary urokinase, although acute closure and in-hospital clinical events were similar to those in patients treated with placebo. To further assess the role of thrombolytic therapy in this circumstance, a larger trial was undertaken with higher doses of urokinase and monitoring of heparin therapy with activated coagulation times.…”
mentioning
confidence: 92%
“…Angiographic resolution of intracoronary thrombus has been variable after intracoronary thrombolysis before angioplasty, but the results have largely been discouraging [5][6][7][8] . As a result, intracoronary thrombolysis is rarely used in clinical practice; however, several studies still support the usefulness of intracoronary thrombolysis in selected cases.…”
Section: A B Cmentioning
confidence: 99%
“…[11][12][13][14][15][16] It also provided the definition used in the Unstable Angina Guidelines. 17 Since the introduction of this classification, considerable progress has been made in understanding the pathophysiology of unstable angina and treatment of this condition.…”
mentioning
confidence: 99%